Taxonomia de Doryctinae (Hymenoptera: Braconidae) na Amazônia brasileira - Gadelha, Sian de Souza (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
Braconidae has about 19,500 valid species, and Doryctinae is one of its most diverse subfamilies with over 1000 species in about 180 genera. However, the authors point out that the greater diversity of the group lies in the Neotropics, where there are about 70% of the genera. In Brazil, have been recorded near 60 genera, 32 for the Brazilian Amazon. However, these genera are known only by their type-localities, and their identification is so hardy due to the lack of keys for the region, and the ones that exist belongs to other regions and are outdated. Thus, the objective here was to conduct a taxonomic study of the Doryctinae genera occurring in the Brazilian Amazon. For its realization, mainly material from Instituto Nacional de Pesquisas da Amazônia (INPA) and Museu Paraense Emílio Goeldi (MPEG) were analyzed, besides other entomological collections of the Amazon region. The material was identified in part through the keys of Marsh (1997 and 2002) to the New World and Costa Rica, respectively and original descriptions. It was possible to analyze more than 900 specimens classified into 44 existing genera, beyond recognition of seven new genera and three new species, all here described. Barbalhoa Marsh, Curtiselloides Marsh, Pannuceus Marsh, Percnobracon Kieffer, Vanderentiellus Marsh and Bolivar Zaldívar- Riverón & Rodríguez-Jiménez are new records for Brazil, while Aphelopsia Marsh, Neoheterospilus Belokobylskij, Panama Marsh and Ptesimogastroides Braet & van Achterberg are news for the Brazilian Amazon region; besides 24 genera had their records expanded within this region. The subfamily was recorded in almost all the states that comprise the Brazilian Amazon, except for Tocantins and Mato Grosso. The largest number of genera was found in Amazonas (44), followed by Pará (23) and Roraima (20). It is suggested that further collection efforts should be concentrated on those states that had fewer genera registered (Rondônia, Mato Grosso, Tocantins and Maranhão) and also have greater risk of loss of biodiversity due to deforestation. The taxonomic analysis suggests the existence of a possible synonymy of Johnsonius Marsh under Semirhytus Szépligeti, and Aphelopsia Marsh under Callihormius Ashmead. The Notiospathius Matthews & Marsh and Allorhogas Gahan have a great diversity within the region and should be studied separately in the future, considering the possibility of discovering new species in the first, and a better definition of it limits in the second.
Keywords: Braconidae; Doryctinae; Ciclóstomos